PENTINGNYA PENDIDIKAN KARAKTER DALAM LEMBAGA FORMAL - hadi, imam (Fakultas Agama Islam UNDARIS, 2019)
Juvenile Delinquencyis a social phenomenon thatdevelops in society such as a clash action and the other moral decadences. Even in big cities, the certain symptoms have arrived at a very disturbing standard. Hence, formal educational institutions as an official receptacleguidance of young generation is expected to enhance its role in the formation of personality students through the increasing of intensity and the quality of education character.The purpose of this research is to find the meaning, the function, the purpose, the features, the principle, the supporting components, the application and the development as well as the character education in achieving the purpose of learning.This research uses qualitativemethodologythat is made in research library ( library research ) directed in understanding muhammad are at a text. The findings obtained is the north american character education to form an educational someone personality through education and action, the result shows in real action that someone with good behavior such as being honest, responsible respect the rights of others, hard work and so on. The function is to expand their base students may grow up to be a good, have with good, and behave well. The aim of this so that the agreement can form the community, competitive, having good, dissolute, bertoleran, bergorong royong, soul patriotic, dynamic, as well as oriented science and technology, all of which imbued by faith, Godfearing to the only one God and at the same time based upon pancasila. The fundamental characteristics in character education regularity the interior of in which every single the act of calculated on the basis of herarki value. The principle to create effective character education is by promotingthe basic ethicalcharacter as its basis. The supporting components in character education are community participation education policy agreement, integrated curriculum, learning experience, evaluation and help parents. Application and development of character education are universal values that can be obtained from religion and developed through the knowledge, knowing as the, and habitual Habit. The character education in achieving the purpose of learning through the increased intensity and number of the quality of character education at an institute formal education.